2008
DOI: 10.1039/b806347h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of iron(ii) spin-crossover

Abstract: We report the synthesis of spin crossover 69 nm spherical nanoparticles of [Fe(NH2-trz)3](Br)2.3H2O.0.03(surfactant) (NH2trz = 4-amino-1,2,4-triazole, surfactant = Lauropal), prepared by the reverse micelle technique, which exhibit at room temperature a thermal hysteresis characterized by magnetic, diffuse reflectivity and Raman studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 18 publications
8
113
0
Order By: Relevance
“…They exhibit a very strong dependence of the spin transition temperature and the character of the transition on the type of the counter anions [2,10], the presence of hydrated water [11], and on the ligand substituent [12,13]. It has been shown that these SCO materials retain the cooperative character of their spin transition also as nanostructures [14][15][16][17][18][19][20][21]. This is important for the application of azole-bridged Fe(II)1D polymer complexes as materials for future molecular electronics and also provides an interesting challenge for theoretical modelling investigations.…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit a very strong dependence of the spin transition temperature and the character of the transition on the type of the counter anions [2,10], the presence of hydrated water [11], and on the ligand substituent [12,13]. It has been shown that these SCO materials retain the cooperative character of their spin transition also as nanostructures [14][15][16][17][18][19][20][21]. This is important for the application of azole-bridged Fe(II)1D polymer complexes as materials for future molecular electronics and also provides an interesting challenge for theoretical modelling investigations.…”
Section: Introductionmentioning
confidence: 99%
“…However, for fundamental studies as well as for practical applications, it still remains an experimental challenge to obtain precise control over the size and the shape of these switchable nanomaterials. Since the first descriptions in 2007 [19][20][21], a lot of works have been devoted to the influence of experimental synthesis parameters on the morphologies, sizes and properties of the [Fe(R-trz) 3 ].X 2 SCO materials: for example, parameters such as the surfactant nature [22,23], the surfactant ratio [23][24][25] and the Fe(II) concentration [26] have been considered. Despite these parameters appearing to influence the final size of the particles, no true rationalization of the synthesis has been done so far.…”
Section: Introductionmentioning
confidence: 99%
“…This included the discovery of several new examples of SCO compounds [3,[9][10][11], the explanation of different types of SCO profiles [4,12] and the modification of SCO compounds to increase cooperativity and to direct their application into materials science [13]. Scientists have developed SCO networks [14][15][16], frameworks [17][18][19], gels [20][21][22], liquid crystals [23][24][25], nanoparticles and nanocrystals [26][27][28][29], nanowires [30], thin films [31][32][33] and have also applied patterning techniques to fabricate SCO devices [34]. Among complexes displaying SCO, [Fe(salEen) 2 ] + derivatives (salEen = N-ethyl-N-(2-aminoethyl)salicylaldiminate) are known to undergo thermal SCO sensitive to unit cell contents and supramolecular packing in the crystal [35].…”
Section: Introductionmentioning
confidence: 99%